2006
DOI: 10.1515/hc.2006.12.3-4.213
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of Novel 1,3-Oxazolidine Nucleoside Analogues

Abstract: The synthesis of novel 1,3-oxazolidine pyrimidine nucleoside analogues are described. These analogues are all derived from the key stereochemically defined intermediate N-tert-butoxy-carbonyl-2hydroxymethyl-l,3-oxazolidine-4-ol which was accessible in 57% yield starting from L-serine methylester hydrochloride. The heterocyclic bases eg; uracil, thymine etc are efficiently introduced onto the 1,3-oxazolidine by the Vorbruggen procedures. The antimicrobial activity of novel 1,3-oxazolidine nucleoside analogues a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…3-Dichloroacetyl-2,2-dimethyl-4-ethyl-1,3-oxazolidine is an anlogue of R-28725 with one chiral center. Most enzymatic reactions in plants are stereoselective; thus, the biological activity of the two optically active enantiomers of 3-dichloroacetyl-2,2-dimethyl-4-ethyl-1,3-oxazolidine and racemate could be different because of their chirality (Kang et al 2005;Sriharsha and Shashikanth 2006). However, few studies have investigated the detoxification mechanisms of chiral safener (Jablonkai 2013).…”
mentioning
confidence: 99%
“…3-Dichloroacetyl-2,2-dimethyl-4-ethyl-1,3-oxazolidine is an anlogue of R-28725 with one chiral center. Most enzymatic reactions in plants are stereoselective; thus, the biological activity of the two optically active enantiomers of 3-dichloroacetyl-2,2-dimethyl-4-ethyl-1,3-oxazolidine and racemate could be different because of their chirality (Kang et al 2005;Sriharsha and Shashikanth 2006). However, few studies have investigated the detoxification mechanisms of chiral safener (Jablonkai 2013).…”
mentioning
confidence: 99%
“…Data collection: APEX2 ; cell refinement: APEX2; data reduction: APEX2; program(s) used to solve structure: SHELXS97 ; program(s) used to refine structure: SHELXL97 ; molecular graphics: ORTEP-3 for Windows (Farrugia,1997) and PLATON ; software used to prepare material for publication: WinGX . (Madhusudhan et al 2004); (Sriharsha & Shashikanth, 2006), antiviral (Wilhelmsson, et al 2008), anti-tumor (Soad et al2006),and anti-inflammatory (Menoret et al 2009). Our investigation is intended to increase the biological activity of such molecules.…”
Section: Special Detailsmentioning
confidence: 99%
“…Studies indicated that some 3-dichloroacetylsubstituted oxazolidines with a chiral center often have different biological activities (Sriharsha & Shashikanth 2006;Zhao et al 2015). One of the most widely used dichloroacetamide safeners in maize was 3-(dichloroacetyl)-2,2,5-trimethyl-1,3-oxazolidine (R-29148).…”
Section: Introductionmentioning
confidence: 99%